Pengaruh Independensi Auditor, Ukuran Kantor Akuntan Publik, dan Professional Judgement Auditor terhadap Kinerja Auditor - Michelle Kristian (Jurnal Ekonomi, 2018)
The objective of this research was to examine the influence of auditor independence, CPA firm size, and auditor’s professional judgement on audit quality. The research was conducted using a survey method to provide the questionnaires to auditors in CPA firms. The data used in this research was primary data. The population of this research is the auditors that work at CPA firm. The sample of this research is auditors that work at CPA firm in Jakarta and Tangerang that have minimum one year of experience in auditing. There are 256 questionnaires distributed for this research, but only 216 questionnaires returned and 127 questionnaires are used in this research using multiple linear regressions. The results of this study were (1) Auditor independence has significant influence on quality, (2) CPA firm size doesn’t have significant influence on audit quality, (3) Auditor’s professional judgement has significant influence on audit quality, (4) Auditor independence, CPA firm size, and auditor’s professional judgement simultaneously have significant influence on auditor performance.